Schoolchild as a health educator for parents regarding hypertension: A quasi-experimental study among school students of South India - Utsav Raj; Poonam Ramesh Naik; Abhay Nirgude (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: An alarming trend of sustained blood pressure elevation among children and adolescents has been found. Health education to schoolchildren in their formative age is the most effective method to be able to modify their habits, and further, they can be enrolled as an effective health educator for their parents. OBJECTIVE: To study the effectiveness of health education module on study participants about prevention and control of hypertension (HTN) and the effectiveness of child as a health educator on parents' knowledge about prevention and control of HTN. MATERIALS AND METHODS: This quasi-experimental study was conducted with a control group among high school students in two urban secondary schools. There were 110 students and 100 parents each in the intervention and control groups. Modular training with interactive teaching-learning methods was conducted for students in the intervention group. They, in turn, educated their parents. RESULTS: Postintervention, the study results showed a higher median for various domains in the intervention group as compared to the control group among both students and parents. On applying Mann-Whitney test, this difference was statistically significant with P < 0.001. CONCLUSION: The increase in the knowledge of parents belonging to the intervention group suggests the effective transfer of knowledge from the students to their parents.